2009
DOI: 10.1182/blood-2007-10-119438
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomic profiling of AML predicts response and survival

Abstract: Because protein function regulates the phenotypic characteristics of cancer, a functional proteomic classification system could provide important information for pathogenesis and prognosis. With the goal of ultimately developing a proteomicbased classification of acute myeloid leukemia (AML), we assayed leukemiaenriched cells from 256 newly diagnosed AML patients, for 51 total and phosphoproteins from apoptosis, cell-cycle, and signal-transduction pathways, using reverse-phase protein arrays. Expression in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(260 citation statements)
references
References 42 publications
10
250
0
Order By: Relevance
“…Cytological FAB subgroups or certain cytogenetic subgroups displayed specific variations of some proteins, and the predictive values of protein profiles have been underscored in acute lymphoblastic leukemia. In AML, the prognostic interest of proteomic approaches was notably demonstrated in a study by Kornblau et al 17 The authors investigated 51 preselected proteins, including 21 phospho-proteins important for apoptosis, cell cycle and signal transduction, using a reverse phase protein array, and showed that seven protein signature groups correlated with relapse and overall survival. Our study provides additional proof of the predictive value of proteomics using a different strategy based on the global evaluation of the protein signature of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytological FAB subgroups or certain cytogenetic subgroups displayed specific variations of some proteins, and the predictive values of protein profiles have been underscored in acute lymphoblastic leukemia. In AML, the prognostic interest of proteomic approaches was notably demonstrated in a study by Kornblau et al 17 The authors investigated 51 preselected proteins, including 21 phospho-proteins important for apoptosis, cell cycle and signal transduction, using a reverse phase protein array, and showed that seven protein signature groups correlated with relapse and overall survival. Our study provides additional proof of the predictive value of proteomics using a different strategy based on the global evaluation of the protein signature of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 Finally, functional proteomic profiling confirmed that specific protein expression patterns correlate with outcome and prognosis, thus providing new molecular classifications useful for predicting the risk of AML patients at diagnosis. 17 In this context, we developed a surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF)-based protein profile of leukemic cells associated with tandem MS (MALDI-TOF/TOF and nanoLC MS/MS) to identify new, specific biomarkers of high-risk AML that are present at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mutated p53, high-level expression of the BCL2-related protein MCL1, and of Neurophilin-1 were identified predicting an adverse outcome for AML patients and a poor clinical prognosis. These data suggest that patients could potentially benefit from combined therapies aiming at inhibiting the anti- apoptotic effect of MCL1 by restoring p53 function via inhibiting MDM2, and this way interfering with signaling through VEGF [44]. The prognostic potential of RPPA was also demonstrated by Petricoin et al in 2007, who first associated the activation of the AKT/mTOR pathway with the therapeutic modulation of pathway activity in childhood rhabdomyosarcoma [26].…”
Section: Potential Use For Monitoring Therapeutic Responsementioning
confidence: 73%
“…The protein data is taken from Kornblau et al (2009) and contains 256 observations on 51 variables. The optimal SG is displayed using the adjacency matrix in Figure 12, the circles represent stratified edges, the triangles edges to which strata could be added while still retaining a decomposable SG, and the squares edges that cannot be stratified in a decomposable SG.…”
Section: Illustrationsmentioning
confidence: 99%